Hubungan Antara Orientasi Penguasaan dan Orientasi Performasi Dengan Intensi Menyontek (The Correlation between Mastery Oriented and Performance Oriented, and Intention of Cheating) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
This study examines the correlation between mastery oriented and per-formance oriented, and intention of cheating. This study employed stratified random sampling technique. The sub-jects of this research were 160 students of four senior high schools of Yogyakarta city. The data for mastery oriented, performance oriented, and intention of cheating were collected using three scales. The data were ana-lyzed using Pearson product moment. Results showed that (1) there was a significant and negative correlation between mastery oriented and intention of cheating (r=0,376